Coronary Radiology - Oudkerk, Matthijs; Reiser, Maximilian F. (Diagnostic Imaging, 2009)
During the past decade, coronary radiology has undergone rapid development. This second edition of the only available monograph on the subject covers the full range of radiological modalities used to examine the coronary arteries and coronary vessel walls. Special emphasis is placed on the role of non-invasive techniques, which can supply information on the condition of the coronary arteries within one simple and short examination. The modalities considered in detail include CT angiography with multidetector and dual-source tomography, 2D and 3D visualization techniques, and MR coronary angiography. Invasive procedures are not neglected, however, and a separate section includes chapters on conventional catheterization, quantitative angiography, and intravascular and quantitative ultrasound. Besides the new acquisition technologies, the substantial improvements made by postprocessing software developers and novel indications for coronary imaging are discussed. A section devoted to coronary calcification clearly explains its development and the use of modern techniques in its visualization and quantification. Furthermore, the latest guidelines on acute chest pain and coronary calcification assessment, written by the key international authorities in the field, are discussed. This important book illustrates how coronary imaging is moving in a direction that will permit the non-invasive acquisition of detailed information on the condition of the coronary arteries in patients worldwide. The text is supported by a large number of high-quality color images of the coronary and cardiac anatomy.